Penerapan Metode Naive Bayes pada Sistem Klasifikasi Kualitas Biji Kopi Robusta - Fata, Muhammad Irsyad Indra; Avianto, Donny (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
In Indonesia, coffee has become a necessity for some people because the effects can increase stamina and mood so that it can make a person's activities more productive, therefore quality coffee beans are needed so that coffee drinks can produce maximum effects and can be enjoyed by the public This is the basis for researchers to conduct research on the classification of superior quality coffee beans with accurate accuracy. Researchers use the naïve Bayes classifier method because this algorithm is considered more effective in cases of object classification compared to classification carried out manually. Researchers used 220 primary data with parameter configurations, namely, test size 0.2, random state 15, and Gausian model. The accuracy results obtained after testing were 0.91 for training data and 0.86 for testing data. It was concluded that the Naive Bayes method proved to be quite effective for classifying the coffee beans studied